Chlorine-based resin composition, electric wire and cable

JP7639469B2Active Publication Date: 2025-03-05PROTERIAL LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021055357
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-29
Publication Date
2025-03-05
Estimated Expiration
2041-03-29

AI Technical Summary

Benefits of technology

【0023】 本発明の一態様のシラングラフト樹脂組成物によれば、電線·ケーブルの被覆材である塩素化ポリエチレンにおいてシラン架橋方式を利用しながらも、過酷な試験条件での耐摩耗性を満足する高い耐久性能を有する材料を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639469000004
    Figure 0007639469000004
  • Figure 0007639469000005
    Figure 0007639469000005
  • Figure 0007639469000001
    Figure 0007639469000001
Patent Text Reader

Abstract

To provide a chlorinated polyethylene to be used for a covering material of an electric wire and cable that has high durability satisfying abrasion resistance under severe test conditions even when treated by a silane cross-linking method.SOLUTION: A chlorine-based resin composition is produced by grafting a silane coupling agent to a base polymer obtained by mixing a chlorinated polyethylene having a Mooney viscosity of 85 or more at 121°C and at four minutes after one minute preheating and an ethylene-vinyl acetate copolymer having a melt mass flow rate of 2.5 g / 10 min or less under a condition of 190°C and 2.16 kgf and a melting point of 80°C or higher in the range of 90:10-50:50 by mass fraction.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a chlorine-based resin composition, an electric wire and a cable. [Background technology]

[0002] In the case of covering materials for electric wires and cables, a crosslinking process is sometimes carried out to chemically bond the molecules of the polymer covering material in order to improve various properties such as heat resistance. The crosslinking process is carried out by mixing a crosslinking agent into the covering material in advance, and then applying energy using heat or electron beams after the cable is covered. However, this method requires large-scale facilities and a large amount of energy. In contrast, the silane crosslinking method bonds a silane coupling agent (hereinafter referred to as silane) to the polymer molecules of the covering material in advance, and then bonds the silanes together (forming crosslinks between polymer molecules) with the action of moisture and a silanol condensation catalyst after the cable is covered. Therefore, the silane crosslinking method does not require large-scale facilities or a large amount of energy, making it an economical and environmentally friendly manufacturing method.

[0003] In applications where flexibility or durability is required, rubber materials are mainly used as covering materials, and the above-mentioned silane crosslinking method is also used to manufacture electric wires and cables. A wide variety of rubber materials are used as covering materials for electric wires and cables, and among them, chlorine-based rubber is known as a high-performance material with excellent flame retardancy and oil resistance.

[0004] Patent Document 1 (JP 2013-41794 A) describes that when producing a resin mixture that constitutes a coating material for an electric wire, a polymer and a filler are kneaded using an internal kneader equipped with two rotors. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2013-41794 A Summary of the Invention [Problem to be solved by the invention]

[0006] Unlike the crosslinking method that controls the degree of crosslinking of the polymer by the amount of crosslinking agent or the dose of electron beam irradiation, the degree of crosslinking of the silane crosslinking method is determined by the amount of silane grafted to the polymer molecule, so the degree of crosslinking is usually relatively low. In the silane crosslinking method, the radicals generated when the organic peroxide is thermally decomposed are used to extract hydrogen from the polymer molecule to graft the silane. For this reason, it is effective to increase the amount of organic peroxide as well as silane to obtain a high degree of crosslinking. However, if the amount of organic peroxide is excessively increased and the amount of radicals generated in the polymer molecule increases, the bonding between polymer molecules (premature crosslinking), which is a side reaction, is promoted, and the fluidity decreases when covering the electric wire / cable, making it easy to cause molding defects. For this reason, the silane crosslinking method can provide a sufficient degree of crosslinking to the covering material for many of the characteristics required as functions of the electric wire / cable (such as heat resistance or oil resistance). However, it is not suitable for products that require particularly high durability (such as abrasion resistance under harsh conditions), such as large-diameter cables, and it has been difficult to achieve such durability.

[0007] Therefore, the present invention aims to provide a material that utilizes the silane crosslinking method in chlorinated polyethylene, which is used as a coating material for electric wires and cables, and that has high durability and satisfies abrasion resistance under severe test conditions.

[0008] Other objects and novel features will become apparent from the description of this specification and the accompanying drawings. [Means for solving the problem]

[0009] [1] The chlorine-based resin composition according to one embodiment of the present invention is a base polymer obtained by grafting a silane coupling agent to the base polymer, which is a mixture of chlorinated polyethylene having a Mooney viscosity of 85 or more after 4 minutes from preheating at 121°C for 1 minute and an ethylene-vinyl acetate copolymer having a melt mass-flow rate of 2.5 g / 10 min or less under conditions of 190°C and 2.16 kgf and a melting point of 80°C or more, in a mass fraction range of 90:10 to 50:50.

[0010] [2] In the above [1], a silanol condensation catalyst is added to the chlorine-based resin composition, and the chlorine-based resin composition is crosslinked by the action of moisture.

[0011] [3] In [2], the silanol condensation catalyst is an octyltin compound, and is added to the chlorine-based resin composition as a masterbatch mixed with a polymer.

[0012] [4] In the above [1] or [2], the silane coupling agent contains a methacryl group as an organic functional group.

[0013] [5] A coil having a conductor and an insulator covering the conductor, body The electric wire is made of a chlorine-based resin composition in which a silane coupling agent is grafted onto a base polymer in which a chlorinated polyethylene having a Mooney viscosity of 85 or more after 4 minutes has elapsed after preheating at 121°C for 1 minute and an ethylene-vinyl acetate copolymer having a melt mass flow rate of 2.5g / 10min or less under conditions of 190°C and 2.16kgf and a melting point of 80°C or more are mixed in a mass fraction range of 90:10 to 50:50, the base polymer being crosslinked by the action of moisture.

[0014] [6] In the above [5], a silanol condensation catalyst is added to the chlorine-based resin composition, and the chlorine-based resin composition is crosslinked by the action of moisture.

[0015] In [7][6], the silanol condensation catalyst is an octyltin compound, and is added to the chlorine-based resin composition as a masterbatch mixed with a polymer.

[0016] In the above-mentioned composition, the silane coupling agent contains a methacryl group as an organic functional group.

[0017] [9] In any one of [5] to [8], the cross-sectional area of ​​the conductor is 38 mm 2 Greater than.

[0018]

[10] A conductor and an insulator covering the conductor. body and a covering material covering the electric wire, the covering material being made of a chlorine-based resin composition obtained by grafting a silane coupling agent to a base polymer in which a chlorinated polyethylene having a Mooney viscosity of 85 or more after 4 minutes has elapsed after preheating at 121°C for 1 minute and an ethylene-vinyl acetate copolymer having a melt mass-flow rate of 2.5 g / 10 min or less under conditions of 190°C and 2.16 kgf and a melting point of 80°C or more are mixed in a mass fraction range of 90:10 to 50:50, the base polymer being a chlorine-based resin composition being crosslinked by the action of moisture.

[0019]

[11]

[10] The chlorine-based resin composition is crosslinked by the action of moisture after a silanol condensation catalyst is added thereto.

[0020] In

[12] and

[11] , the silanol condensation catalyst is an octyltin compound, and is added to the chlorine-based resin composition as a masterbatch mixed with a polymer.

[0021]

[13] In the above

[10] or

[11] , the silane coupling agent contains a methacryl group as an organic functional group.

[0022]

[14] In any one of

[10] to

[13] , the cross-sectional area of ​​the conductor is 38 mm 2 Greater than. Effect of the Invention

[0023] According to the silane graft resin composition of one embodiment of the present invention, a material having high durability performance that satisfies abrasion resistance under severe test conditions can be provided while utilizing a silane crosslinking method in chlorinated polyethylene, which is a coating material for electric wires and cables. [Brief description of the drawings]

[0024] [Figure 1] FIG. 2 is a schematic diagram showing an extruder for producing cables used in the present embodiment and the comparative examples. [Diagram 2] FIG. 2 is a cross-sectional view showing the produced cable. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings. In all the drawings for explaining the embodiments, the same reference numerals are used for the members having the same functions, and the repeated explanations are omitted. In the following embodiments, the explanations of the same or similar parts will not be repeated as a rule, unless it is particularly necessary.

[0026] (Embodiment) Cab-tyre cables are an example of a general-purpose cable coated with rubber material. Cab-tyre cables are classified into fixed and movable types depending on the purpose of use. Of these, movable cables are required to have flexibility against repeated bending and abrasion resistance against rubbing in various environments, as the cable itself moves. For abrasion resistance in particular, test conditions are set according to the cable size, and the Electrical Appliance and Material Safety Act (Appendix 1) and JIS C3327 state that for multi-core cables with a conductor cross-sectional area of ​​38 mm 2 In order to be able to withstand such severe test conditions, the inventors have investigated the following method to improve the abrasion resistance of the silane cross-linked chlorinated polyethylene material that is the cable coating material.

[0027] The first method is to increase the degree of cross-linking. If an excessive amount of organic peroxide is added to increase the amount of grafted silane, cross-linking between polymers will progress, which may cause defects such as rough appearance or bumps when the cable is molded. It is possible to suppress cross-linking between polymers to some extent by increasing the amount of silane added together with the organic peroxide, but this is not a practical solution because it causes the material to soften, resulting in a decrease in tensile strength and abrasion resistance, a decrease in electrical insulation, and an increase in material costs.

[0028] The second method is the application of chlorinated polyethylene with high crystallinity. Chlorinated polyethylene is mainly produced from high density polyethylene as a raw material, and various grades are produced in which relatively strong crystals derived from high density polyethylene remain. Therefore, the present inventors considered applying chlorinated polyethylene with high crystallinity to the silane crosslinking material. However, although the abrasion resistance of the coating material is improved, it was found that the coating material becomes excessively hard and the flexibility required for a rubber material is significantly impaired, so the application was abandoned.

[0029] The third method is the application of chlorinated polyethylene with a high molecular weight. By lengthening the molecular chain, the entanglement between molecules increases, and it is expected that the abrasion resistance will be improved. When the inventors of the present invention examined the application of this method to silane crosslinking materials, they found that the abrasion resistance improved as expected, but the viscosity of the coating material increased, which caused a high load to be applied when coating the cable in an extruder, making molding difficult. One countermeasure is to reduce the viscosity of the material by extrusion at high temperatures, but this is not practical because chlorine-based materials such as chlorinated polyethylene may undergo significant deterioration due to the elimination of chlorine (as hydrogen chloride) in a high-temperature environment. Therefore, in order to improve the heat flowability during extrusion, they considered alloying an ethylene-vinyl acetate copolymer that shows high compatibility with chlorinated polyethylene and is capable of silane grafting using organic peroxides like chlorinated polyethylene, and grafting silane onto this alloy material. As a result of extensive investigations, the inventors have found conditions that enable both abrasion resistance under severe test conditions and good moldability during cable extrusion coating to be achieved by appropriately controlling the mixing ratio of the two materials while controlling the Mooney viscosity, which is an indicator of molecular weight, for chlorinated polyethylene, and the melting point, which is correlated with the melt mass flow rate, which is an indicator of thermal fluidity, and the crystal content, which strongly affects abrasion resistance, for ethylene-vinyl acetate copolymer.

[0030] <Specific configuration> The chlorine-based resin composition of the present embodiment is formed by controlling the mixing ratio of both materials within an appropriate range while limiting the Mooney viscosity (121°C, value after 4 minutes after 1 minute preheating) of the chlorinated polyethylene as the base polymer, the melting point (80°C or higher) and the melt mass flow rate (190°C, 2.16 kgf) of the ethylene-vinyl acetate copolymer. Here, the chlorinated polyethylene is selected to have a practical Mooney viscosity of about 120 or less, and although there are no limitations on physical properties other than the Mooney viscosity, the chlorine content may be 20 to 45 mass% and the crystallization amount (DSC heat of fusion) may be 5 J / g or less. In addition, it is more preferable that the chlorine content of the chlorinated polyethylene is 25 to 40 mass% and the crystallization amount is 2 J / g or less in terms of the balance between flame retardancy and flexibility. Furthermore, for practical purposes, ethylene vinyl acetate copolymers having a melting point of 95° C. or less and a melt mass flow rate of 0.5 g / 10 min or more are selected, with no limitations placed on physical properties other than the melting point and melt mass flow rate.

[0031] With respect to a material, the melt mass flow rate is an index of fluidity (an index of molecular weight (length of molecule)). A high melt mass flow rate means high fluidity and a small molecular weight (short molecule), which reduces abrasion resistance. In other words, the longer the molecule, the easier it is to crosslink, form bonds between molecules, and physically entangle with each other, improving the abrasion resistance of the material. Here, the abrasion resistance of the chlorine-based resin composition is improved by using an ethylene-vinyl acetate copolymer with a melt mass flow rate of 2.5 g / 10 min or less under conditions of 190°C and 2.16 kgf.

[0032] In addition to molecular weight, increasing the melting point, which is correlated with the amount of crystals in a molecule, increases the amount of crystals and improves the wear resistance of the material. This is because crystals are folded molecules and exist as strong parts (parts resistant to wear) in the material.

[0033] The silane coupling agent may be any one having an organic functional group and an alkoxy group that exhibits an addition reaction to radicals. For example, a general-purpose silane coupling agent having an organic functional group such as a vinyl group, a methacryl group, an acryl group, or a styryl group, and an alkoxy group such as a methoxy group or an ethoxy group, is used. Specifically, vinyltrimethoxysilane, vinyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-acryloxypropyltrimethoxysilane, p-styryltrimethoxysilane, or a mixture thereof may be mentioned. However, as long as it has both the above-mentioned organic functional group and the alkoxy group, it may be an alkoxy oligomer, and is not limited to the above-mentioned compounds.

[0034] The chlorine-based resin composition (silane-grafted rubber composition) may be mixed with additives such as an organic peroxide for grafting silane, or a hydrogen chloride scavenger for efficiently capturing hydrogen chloride that may be generated from the chlorinated polyethylene, as well as a plasticizer, a lubricant, a reinforcing agent, a filler, or a flame retardant.

[0035] Here, examples of organic peroxides that can be used include dicumyl peroxide, 1,1-di(t-butylperoxy)cyclohexane, t-butylperoxyisopropyl carbonate, t-amylperoxyisopropyl carbonate, 2,5 dimethyl 2,5 di(t-butylperoxy)hexane, di-t-butyl peroxide, di-t-amyl peroxide, 1,1-di(t-amylperoxy)cyclohexane, and t-butylperoxy 2-ethylhexyl carbonate. These can be used alone or in combination of two or more kinds, but are not limited thereto.

[0036] Examples of hydrogen chloride scavengers include epoxy group-containing compounds, hydrotalcites, lead-containing compounds such as tribasic lead sulfate, tin-containing compounds, and metal soaps.

[0037] Furthermore, by adding an antioxidant or a silanol condensation catalyst to the chlorine-based resin composition, it is possible to improve heat resistance and promote the crosslinking reaction. These can inhibit the silane graft reaction or cause molding defects, so it is better to mix them with the chlorine-based resin composition at the time of final molding (at the time of extrusion coating on the conductor or cable core in the case of electric wires and cables).

[0038] Examples of the silanol condensation catalyst include elements or metal compounds of Group II elements such as magnesium and calcium, Group VII elements such as cobalt and iron, or elements such as tin, zinc, and titanium, metal salts of octylic acid or adipic acid, amine compounds, acids, etc. More specifically, examples of the silanol condensation catalyst include inorganic acids such as dioctyltin dineodecanoate, dibutyltin dilaurate, dibutyltin diacetate, dibutyltin dioctaate, stannous acetate, stannous caprylate, lead naphthenate, zinc caprylate, cobalt naphthenate, ethylamine, dibutylamine, hexylamine, pyridine, sulfuric acid, and hydrochloric acid, and organic acids such as toluenesulfonic acid, acetic acid, stearic acid, and maleic acid.

[0039] As described above, in this embodiment, a chlorine-based resin composition is provided in which a silane coupling agent is grafted to a base polymer in which a chlorinated polyethylene having a Mooney viscosity of 85 or more after 4 minutes from 121°C preheating and an ethylene-vinyl acetate copolymer having a melting point of 80°C or more and a melt mass flow rate of 2.5g / 10min or less under conditions of 190°C and 2.16kgf are mixed in a mass fraction range of 90:10 to 50:50. The chlorine-based resin composition having such a configuration can be used as an insulator or sheath material for covering materials for electric wires and cables.

[0040] In addition, silane coupling agents having unsaturated bonds in the molecule that react with radicals have a relatively high flash point, and as they have excellent fire safety when mixed into polymers, methacryl group-containing silane coupling agents can be used. Examples of such silane coupling agents include 3-methacryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane.

[0041] In addition, as the silanol condensation catalyst, an octyltin compound that is a tin-based compound with high catalytic activity and does not contain dibutyltin, which is considered to have a relatively large environmental load, can be used. Examples of such octyltin include dioctyltin dineodecanoate and dioctyltin dilaurate. In addition, since the silanol condensation catalyst can be added in small amounts to the chlorine-based resin composition, it is useful from the viewpoint of quality stability and industrial use to add it to the chlorine-based resin composition as a high-concentration master batch.

[0042] In addition, the chlorine-based resin composition of the present embodiment is suitable for use in a multi-core cable that satisfies the severest abrasion test conditions prescribed in the Electrical Appliance and Material Safety Law (Appendix 1) and JIS C3327, which is a conductor cross-sectional area of ​​38 mm 2 It can be applied to wire and cable coating materials with large diameters exceeding 100mm.

[0043] <Chlorine-based resin composition and method for producing cable> The chlorine-based resin composition and the method for producing the cable will be described below.

[0044] The following steps are carried out in the order listed below: mixing silane and various additives with a mixture of chlorinated polyethylene and ethylene vinyl acetate copolymer, silane grafting, cable production using the compound, and post-treatment. The following conditions are merely examples and are not intended to be limiting.

[0045] (Mixing silane and various additives) Chlorinated polyethylene, ethylene vinyl acetate copolymer, silane coupling agent, organic peroxide, hydrogen chloride scavenger, plasticizer, lubricant, reinforcing agent, filler and flame retardant were put into a 25L pressure kneader (the kneader tank was adjusted to a temperature of 100°C), and pressurized and kneaded for 10 minutes at a rotor speed of 10 rpm. Here, the organic peroxide can be dissolved in the silane coupling agent in advance to improve the dispersibility of the organic peroxide in the polymer. In addition, the silane coupling agent (dissolving the organic peroxide) can be impregnated into the filler such as the reinforcing agent at the time of input to reduce the adsorption of the silane coupling agent in the kneader tank. In addition, by adding the ethylene vinyl acetate copolymer at the end of the kneading, the viscosity of the material during kneading of the additives can be increased to improve the dispersibility. These conditions are only examples and are not limited.

[0046] (Silane grafting treatment) After the above kneading, the material is kneaded and heated to 180°C at a rotor speed of 30 rpm using the same device (a 25L pressure kneader, the kneader is adjusted to a temperature of 100°C). This operation can be performed continuously without discharging the material after the above kneading. After reaching 180°C, the rotation speed is reduced and the material is isothermally kneaded for 3 minutes and 30 seconds to dynamically graft the silane coupling agent to the polymer. After the grafting is completed, the material is quickly discharged into a single-screw extruder hopper, extruded into a strand shape, cooled with water, and pelletized to produce pellets of the chlorine-based resin composition. Here, the granulation method is not limited to the above, and for example, pellets may be produced using a hot cut facility without water cooling. In addition, a release agent can be used to prevent adhesion between pellets. The release agent can be any component or any form such as powder, liquid, or mist, but it is effective to use talc, for example, in consideration of economic efficiency.

[0047] (Preparation of master batch pellets) The polymer (in the case of chlorine-based materials, a hydrogen chloride scavenger can also be used), antioxidant, and silanol condensation catalyst are charged into the same 25 L pressure kneader (kneader tank temperature controlled at 100°C) as above, and pressure kneading is performed for 10 minutes at a rotation speed of 10 rpm. The polymer may be the same chlorinated polyethylene and ethylene vinyl acetate copolymer as the main material, but is not particularly limited. As with the silane grafting treatment described above, the kneaded material is granulated into pellets, and a release agent may be used to prevent the pellets from sticking to each other.

[0048] (Cable manufacturing and cross-linking) Conductor cross-sectional area 50mm made of multiple strands of tin-plated soft copper wire 2 A conductor (outer diameter 10.4 mm) is extruded with an ethylene-propylene rubber copolymer blend as an insulator to a thickness of 1.5 mm. Next, a cable core, which is a cable made by twisting three crosslinked wires, is dry-blended with pellets of a chlorine-based resin composition and a master batch, and extruded to a thickness of 3.3 mm using a single-screw extruder with a screw diameter of 90 mm to produce a cable. Here, the finished outer diameter of the cable is about 36 mm. The cable after production is stored in a saturated water vapor atmosphere at 60°C for 24 hours to perform a crosslinking treatment. That is, after the cable is coated, the silanes are bonded together (crosslinks are formed between polymer molecules) by the action of moisture and a silanol condensation catalyst. That is, the chlorine-based resin composition is crosslinked to become a silane-crosslinked rubber composition. The dry blending performed here is performed by mixing two or more types of pellets manually or mechanically in a bag or a kettle.

[0049] In order to achieve the above kneading and grafting, any commonly used kneading and reaction device such as a roll machine, an extruder, a mixer, or an autoclave other than a kneader can be used. Moreover, the kneading and grafting conditions are not limited to those described above. Similarly, the above-mentioned cable manufacturing method is an example, and the extruder, the cable core, the cable structure, and the crosslinking conditions are not limited to those described above. Here, the use of the chlorine-based resin composition of the present embodiment as a sheath material in the manufacture of a cable has been described, but the chlorine-based resin composition may be used as an insulator that is a covering material for a conductor. In other words, the chlorine-based resin composition may be used for both the insulator that constitutes the core and the sheath that covers the core.

[0050] <Example> Examples and comparative examples of this embodiment will be described below with reference to FIGS. 1, 2 and Tables 1 to 3.

[0051] The present inventors produced a chlorine-based resin composition, a master batch, and a cable using the equipment, cable structure, cable production extrusion conditions, and material blends shown in Figures 1, 2, and Tables 1 to 3. The characteristics of the cable crosslinked with the silane graft composition were evaluated as follows.

[0052] The schematic diagram of Fig. 1 shows an extruder for producing cables used in the present embodiment and the comparative example. As shown in Fig. 1, the extruder 1 includes a cylinder 5, a screw 3 rotatably provided in the cylinder 5, a hopper 2 for supplying material into the cylinder 5, and a crosshead 7. The extruder 1 also includes a neck 6 between the crosshead 7 and the screw 3, and a breaker plate 4 between the neck 6 and the screw 3. The crosshead 7 has a die 8, and a core 9 passing through the crosshead 7, i.e., a conductor covered with an insulator, is covered with a sheath in the crosshead 7, passes through the die 8, and is drawn out of the crosshead 7 as a cable 10.

[0053] Fig. 2 is a cross-sectional view showing a cable produced by the extruder 1. As shown in Fig. 2, the cable 10 is made by twisting three cores 9 together and covering them with a sheath 13. The cores 9 have a cross-sectional area of ​​50 mm 2 The cable is made up of a conductor 11 and an insulator 12 that covers the conductor 11. The insulator 12 is made of, for example, an ethylene-propylene rubber copolymer blend. The sheath 13 covers all three cores 9.

[0054] The diameter of the conductor 11 is, for example, 10.4 mm. The diameter of the core 9 is, for example, 13.4 mm. The diameter of the cable 10 is, for example, 36 mm. The shortest distance between the core 9 and the outer circumferential surface of the sheath 13 is, for example, 3.3 mm.

[0055] Table 1 below shows the extrusion conditions in the cable extrusion process. Table 2 shows the compositions and evaluation results in Examples 1 to 7. Table 3 shows the compositions and evaluation results in Example 8 and Comparative Examples 1 to 6. The flange shown in Table 1 is the end of the cylinder 5, that is, the end on the neck 6 side.

[0056] [Table 1]

[0057] [Table 2]

[0058] [Table 3]

[0059] Of the products shown in Tables 2 and 3, "CM3685" and "CM352L" are manufactured by Kori Chemical (China), "Elaslen 401A" is manufactured by Showa Denko, "EV270", "EV460", "EV450", "V5274", and "EV550" are manufactured by Mitsui Dow Polychemicals. In addition, of the products shown in Tables 2 and 3, "VF-120T" is manufactured by Ube Maruzen Polyethylene, "KBM-503" is manufactured by Shin-Etsu Chemical, "DCP" is manufactured by NOF, and "Carbon Black" is HTC#S (arithmetic mean particle size 68 nm) manufactured by Nippon Steel Carbon.

[0060] Among these, the Mooney viscosity of CM3685 is 85, the Mooney viscosity of CM352L is 55, and the Mooney viscosity of Elaslen 401A is 115. The melting point of EV270 is 72°C, and the melt mass flow rate is 1g / 10min. The melting point of VF120T is 85°C, and the melt mass flow rate is 1g / 10min. The melting point of EV460 is 84°C, and the melt mass flow rate is 2.5g / 10min. The melting point of EV450 is 84°C, and the melt mass flow rate is 15g / 10min. The melting point of V5274 is 89°C, and the melt mass flow rate is 0.8g / 10min. The melting point of EV550 is 89°C, and the melt mass flow rate is 15g / 10min.

[0061] (1) Wear characteristics (wear resistance) Tests were conducted in accordance with JIS C 3005 using the cross-linked cables. The weight had a mass of 10 kg, and the grinding wheel disc rotated 1000 times. After the test, those in which the insulation was not exposed were rated as good (denoted as ◯ or ◎ in Tables 2 and 3), and those in which the insulation was exposed were rated as bad (denoted as × in Tables 2 and 3). For those in which the insulation was not exposed, the depth of the worn area was calculated using a micrometer from the following formula (1), and those that were less than 3.0 mm were judged to have particularly excellent wear resistance (denoted as ◎ in Tables 2 and 3).

[0062] Abrasion depth = Cable outer diameter before test - Cable thickness at the abraded part after test (1) (2) Mooney viscosity (processability) The Mooney viscosity at 130°C (value after 4 minutes after 1 minute preheating) was measured using the composition after the silane grafting treatment. The lower the Mooney viscosity, the smaller the load during cable extrusion and the better the processability. In actual production, the lower the viscosity, the greater the discharge amount and the higher the cable extrusion speed. Furthermore, the lower the viscosity, the less likely extrusion distortion remains during high-speed extrusion, and the lower the viscosity is, the more advantageous it is that heat shrinkage after cable installation can be suppressed. A Mooney viscosity of less than 60 was rated as good (marked ◯ or ◎ in Tables 2 and 3), and a Mooney viscosity of 60 or more was rated as poor (marked × in Tables 2 and 3). A Mooney viscosity of less than 50 was judged to be particularly excellent in processability (marked ◎ in Tables 2 and 3).

[0063] (3) Overall Judgment In the above (1) and (2), if both characteristics were good, it was marked as pass (marked with ◯ or ◎ in Tables 2 and 3), and if either one was poor, it was marked as fail (marked with × in Tables 2 and 3).

[0064] From the examples, it was found that the wear resistance improves with an increase in the amount of chlorinated polyethylene added, and the processability improves with an increase in the amount of ethylene-vinyl acetate copolymer added. It was also found that by making the mixing mass ratio of chlorinated polyethylene and ethylene-vinyl acetate copolymer 90:10 to 50:50, both wear resistance and processability can be achieved, and further, by adjusting the ratio to 70:30, excellent properties in both wear resistance and processability can be obtained.

[0065] In contrast, Comparative Examples 1 and 2 showed that excessively increasing the addition ratio of chlorinated polyethylene leads to poor processability, and excessively increasing the addition ratio of ethylene-vinyl acetate copolymer leads to poor abrasion resistance. Comparative Example 3 showed that excessively decreasing the Mooney viscosity of the chlorinated polyethylene itself (reducing the molecular weight too much) leads to a decrease in abrasion resistance. Comparative Examples 4 to 6 confirmed that decreasing the melting point of the ethylene-vinyl acetate copolymer or increasing the melt mass flow rate leads to a decrease in abrasion resistance.

[0066] In Comparative Example 3, the Mooney viscosity of CM352L is 85 or less (specifically, 55), so the abrasion resistance is judged to be poor. In Comparative Examples 5 and 6, the melt mass flow rate of the ethylene-vinyl acetate copolymer is not 2.5 g / 10 min or less, so the abrasion resistance is judged to be poor.

[0067] From the above, it was found that in order to achieve both abrasion resistance and processability, in addition to the Mooney viscosity (molecular weight) of the chlorinated polyethylene itself and the melting point and melt mass flow rate of the ethylene-vinyl acetate copolymer, the mixing ratio of the two materials is important, and that by appropriately controlling these, the desired characteristics can be obtained.

[0068] In the present embodiment, a chlorine-based resin composition having good processability while satisfying abrasion resistance under severe conditions and an electric wire / cable coated therewith can be produced, while using silane crosslinking, which is an energy-saving and highly economical crosslinking method for electric wires / cables.

[0069] The present invention is not limited to the above-described embodiment and examples, and various modifications can be made without departing from the spirit and scope of the present invention. [Explanation of symbols]

[0070] 1. Extruder 2. Hopper 3 Screw 5 Cylinder 8 Dice 9 cores 10 Cable

Claims

1. A chlorine-based resin composition in which a silane coupling agent is grafted onto a base polymer obtained by mixing, in a mass fraction range of 90:10 to 50:50, chlorinated polyethylene having a Mooney viscosity of 85 or more after 4 minutes have elapsed after preheating at 121°C for 1 minute and an ethylene-vinyl acetate copolymer having a melt mass flow rate of 2.5 g / 10 min or less under conditions of 190°C and 2.16 kgf and a melting point of 80°C or more.

2. The chlorine-based resin composition according to claim 1, A chlorine-based resin composition to which a silanol condensation catalyst has been added and which is crosslinked by the action of moisture.

3. The chlorine-based resin composition according to claim 2, The silanol condensation catalyst is an octyltin compound and is added to the chlorine-based resin composition as a masterbatch mixed with a polymer.

4. The chlorine-based resin composition according to claim 1 or 2, The silane coupling agent is a chlorine-based resin composition containing a methacryl group as an organic functional group.

5. A conductor; an insulator covering the conductor; having The insulator is made of a chlorine-based resin composition in which a silane coupling agent is grafted onto a base polymer in which a chlorinated polyethylene having a Mooney viscosity of 85 or more after 4 minutes has elapsed after preheating at 121°C for 1 minute and an ethylene-vinyl acetate copolymer having a melt mass flow rate of 2.5 g / 10 min or less under conditions of 190°C and 2.16 kgf and a melting point of 80°C or more are mixed in a mass fraction range of 90:10 to 50:50, The chlorine-based resin composition is crosslinked by the action of moisture.

6. The electric wire according to claim 5, The chlorine-based resin composition has a silanol condensation catalyst added thereto and is crosslinked by the action of moisture.

7. The electric wire according to claim 6, The silanol condensation catalyst is an octyl tin compound and is added to the chlorine-based resin composition as a masterbatch mixed with a polymer.

8. The electric wire according to claim 5 or 6, The electric wire, wherein the silane coupling agent contains a methacryl group as an organic functional group.

9. The electric wire according to any one of claims 5 to 8, The cross-sectional area of ​​the conductor is 38 mm 2 Bigger, electric wire.

10. An electric wire including a conductor and an insulator covering the conductor; A coating material that coats the electric wire; having The coating material is made of a chlorine-based resin composition in which a silane coupling agent is grafted onto a base polymer in which a chlorinated polyethylene having a Mooney viscosity of 85 or more after 4 minutes has elapsed after preheating at 121°C for 1 minute and an ethylene-vinyl acetate copolymer having a melt mass flow rate of 2.5 g / 10 min or less under conditions of 190°C and 2.16 kgf and a melting point of 80°C or more are mixed in a mass fraction range of 90:10 to 50:50, A cable, wherein the chlorine-based resin composition is crosslinked by the action of moisture.

11. 11. The cable of claim 10, A cable, wherein the chlorine-based resin composition contains a silanol condensation catalyst added thereto and is crosslinked by the action of moisture.

12. 12. The cable according to claim 11, The silanol condensation catalyst is an octyl tin compound and is added to the chlorine-based resin composition as a masterbatch mixed with a polymer.

13. 12. The cable according to claim 10 or 11, A cable, wherein the silane coupling agent contains a methacryl group as an organic functional group.

14. The cable according to any one of claims 10 to 13, The cross-sectional area of ​​the conductor is 38 mm 2 Bigger, cable.

Citation Information

Patent Citations

  • Polymer blend composition

    JP1991041139A

  • Silane-crosslinked polyolefin molded article

    JP2003034745A

  • Wire / cable and composition

    JP2013041794A

  • Catalyst batch, wire and cable formed by using the same and manufacturing method therefor

    JP2018044032A

  • Chlorine-containing crosslinked resin molded body and method for producing the same, silane masterbatch, masterbatch mixture and molded body of the same, and molded product

    JP2018172514A